Martin SCHLAG y Boglárka KOLLER, Rethinking Subsidiarity. Multidisciplinary Reflections on the Catholic Social Tradition, Cham: Springer, 2024, 225 pp., 15,5 x 23,4, ISBN 978-3-031-50145-6. (Scripta Theologica, 2024)
Book Review